ANALYSIS OF OBSTACLES IN IMPLEMENTING HEALTHY LIFESTYLE BEHAVIORS THROUGH BALANCED NUTRITIONAL EATING - Sumiati Sumiati; Rr. Dina Kusuma Wardhani; Ratih Kusumawardani (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
Understanding of healthy food consumption patterns continues to evolve along with advances in science and technology. Therefore, an appropriate concept is needed for effective implementation. This study aims to identify the types of food and drinks children bring to school every day, examine the obstacles parents face in preparing nutritionally balanced lunches, and analyze various factors that influence school consistency in supporting the habit of bringing healthy lunches to children. This study used a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The data analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions. The data sources in this study involved school principals, teachers, and parents. The results showed that the variety of lunches brought by children to school did not fully meet the principles of balanced nutrition. On the other hand, most parents did not experience significant obstacles in preparing lunches. Factors influencing school consistency in implementing the habit of bringing nutritionally balanced lunches include the level of understanding of educators, the implementation of school programs, and support from the school environment.